Integrity of Authenticity and Real Presence in The Couple in the Cage - Kiewan Foxe (Caribbean Studies Students' Union, 2022)
With performance often being used as a means of entertainment for many, audiences can sometimes be at fault for allowing their gullibility to fiction and historical inaccuracies led to dangerously self-constructed beliefs. Time and time again with regard to the colonial history of Indigeneity in the "New World," we face the risk of falling victim to historical deceit. Coco Fusco and Guillermo Gómez-Peña's performance, The Couple in the Cage: A Guatinaui Odyssey, is a masterfully produced stage play that reveals flaws in past and present historical beliefs that were strengthened by almost laughable false colonial narratives. Highlighting the ignorance to Indigeneity in Western mind, the two performers lead the viewer to question their relationship with the history of oppressed societies or "the Other." This analysis seeks to consider the significance of The Couple in the Cage: A Guatinaui Odyssey in the context of the fragility and danger of colonial credence that leaves "the Other" as a victim of falsehoods.